Interaksi Sosial dalam Permainan Musik dalam Grup Orkes Keroncong Gema Wredatama di Kota Magelang - Rahoetomo, Rooskartiko Bagas; Haryono, Slamet (Jurnal Seni Musik, 2017)
Music art activities can be done by anyone, ranging from children to the elderly. It can be a group or a community which in the art process has a process of social interaction. How music is used as a means of interaction in the activities of art. The research method used in this research is qualitative descriptive. Technique of collecting data by observation, interview and study of documentation with technique of data validity used triangulation data. The results showed that in an artistic activity has a pattern of interaction vertically and horizontally. Patterns of interaction vertically and horizontally can be seen in the interaction between the PWRI board and members, the chairman of the keroncong grup to members and trainers to the members. But in the relationship between the musical instrument players in this group, the pattern of communication is more dominated by vertical communication patterns. Mean while the interaction between the singers, the pattern of communication that occurs more dominated is horizontally communication. Based on the results of research and discussion it can be concluded that in the art activities within this group, the interaction can be divided into two kinds. The interaction forms a communication pattern that is horizontal communication and vertical communication which happen between the involved actors.